The Influence of Buckling Mode and Buckling Stability Coefficient of Rigid-Frame Bridge during Construction in Cold Region. (16th July 2022) - Li, Jiangjiang; Zhang, Xuanyu; Wang, Xiandong
Abstract : The study aims to further standardize the construction process, improve the construction quality, and ensure the stability of infrastructure construction. The continuous rigid-frame bridge is taken as the research object, the finite element model of the bridge body is established by using the beam element, and the overall stability of the rigid-frame bridge is analyzed in the construction and completion stages. Moreover, the stability coefficient and buckling mode are established under different working conditions in each stage, the linear stability variation law is summarized, and the geometric nonlinear stability analysis method is established through the specific data. The nonlinear stability safety factor and buckling mode are obtained, and the influence of wind load and initial defects on the stability of continuous rigid-frame bridge is further explored. The results show that with the increase of the bridge height, the overall stability factor of the bridge is decreasing, and the safety factor of the single-limb thin-walled hollow pier is relatively larger than that of the double-limb thin-walled hollow pier. During the construction, the asymmetric self-weight load caused by the asynchronous load and cantilever pouring has the greatest impact on the stability of the bridge. The stability safety factor of the geometric nonlinear stability analysis method constructed is 0.3% and 1.27% lower than the ideal state, respectively. The stability safety factor of the wind load and the initial defect is 12.65% lower than the ideal state, and the stability safety factor is greatly reduced. The results have important reference significance to ensure the construction safety and overall stability of the bridge.